2019
DOI: 10.1021/acs.jproteome.9b00118
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Citrullinated Sites in Multiple Organs of Mice Using Hypercitrullinated Library

Abstract: Protein citrullination (or deimination), an irreversible post-translational modification, has been implicated in several physiological and pathological processes, including gene expression regulation, apoptosis, rheumatoid arthritis, and Alzheimer’s disease. Several research studies have been carried out on citrullination under many conditions. However, until now, challenges in sample preparation and data analysis have made it difficult to confidently identify a citrullinated protein and assign the citrullinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(67 citation statements)
references
References 53 publications
6
61
0
Order By: Relevance
“…48 Consistent with the report by Lee et al, 42 the largest number of citrullinated proteins in this study was found in the brain and lung. 48 In addition, unique cellular diversity of the citrullinated proteins suggests a broad biological role for protein citrullination. In summary, to pinpoint true-positive citrullination annotations, the citrullinated residue must be distinguished from deaminated residue.…”
Section: Hydrophobicity and Peptide Elusion In The Analysis Of Citrsupporting
confidence: 93%
See 4 more Smart Citations
“…48 Consistent with the report by Lee et al, 42 the largest number of citrullinated proteins in this study was found in the brain and lung. 48 In addition, unique cellular diversity of the citrullinated proteins suggests a broad biological role for protein citrullination. In summary, to pinpoint true-positive citrullination annotations, the citrullinated residue must be distinguished from deaminated residue.…”
Section: Hydrophobicity and Peptide Elusion In The Analysis Of Citrsupporting
confidence: 93%
“…To overcome this problem, Fert‐Bober et al came up with the idea of hypercitrullination library creation. The hypercitrullinated library allows for enrichment of the lower abundance citrullinated peptides to be detected by the DIA MS approach.…”
Section: Mass Spectrometry Applied To the Study Of Citrullination In supporting
confidence: 81%
See 3 more Smart Citations